Ex vivo visualization of human ciliated epithelium and quantitative analysis of induced flow dynamics by using optical coherence tomography. Issue 3 (23rd February 2017) - Ling, Yuye; Yao, Xinwen; Gamm, Ute A.; Arteaga‐Solis, Emilio; Emala, Charles W.; Choma, Michael A.; Hendon, Christine P.
Abstract : Background and Objective: Cilia‐driven mucociliary clearance is an important self‐defense mechanism of great clinical importance in pulmonary research. Conventional light microscopy possesses the capability to visualize individual cilia and its beating pattern but lacks the throughput to assess the global ciliary activities and flow dynamics. Optical coherence tomography (OCT), which provides depth‐resolved cross‐sectional images, was recently introduced to this area. Materials and Methods: Fourteen de‐identified human tracheobronchial tissues are directly imaged by two OCT systems: one system centered at 1, 300 nm with 6.5 μm axial resolution and 15 μm lateral resolution, and the other centered at 800 nm with 2.72 μm axial resolution and 5.52 μm lateral resolution. Speckle variance images are obtained in both cross‐sectional and volumetric modes. After imaging, sample blocks are sliced along the registered OCT imaging plane and processed with hematoxylin and eosin (H&E) stain for comparison. Quantitative flow analysis is performed by tracking the path‐lines of microspheres in a fixed cross‐section. Both the flow rate and flow direction are characterized. Results: The speckle variance images successfully segment the ciliated epithelial tissue from its cilia‐denuded counterpart, and the results are validated by corresponding H&E stained sections. A further temporal frequency analysis is performed to extract the ciliary beat frequency (CBF) at cilia cites. By adding polyester microspheres as contrast agents, we demonstrate ex vivo imaging of the flow induced by cilia activities of human tracheobronchial samples. Conclusion: This manuscript presents an ex vivo study on human tracheobronchial ciliated epithelium and its induced mucous flow by using OCT. Within OCT images, intact ciliated epithelium is effectively distinguished from cilia‐denuded counterpart, which serves as a negative control, by examining the speckle variance images. The cilia beat frequency is extracted by temporal frequency analysis. The flow rate, flow direction, and particle throughput are obtained through particle tracking. The availability of these quantitative parameters provides us with a powerful tool that will be useful for studying the physiology, pathophysiology and the effectiveness of therapies on epithelial cilia function, as well as serve as a diagnostic tool for diseases associated with ciliary dysmotility. Lasers Surg. Med. 49:270–279, 2017. © 2017 Wiley Periodicals, Inc.